PERILAKU EKONOMI DALAM JEJARING MASYARAKAT KONSUMSI PERKOTAAN - Rini, Hartati Sulistyo (Forum Ilmu Sosial, 2012)
Consumer society is what is called as one of the major influences in the economic system of capitalistic. As a social phenomenon, the consumer society has the typical characteristics, according to the characteristics of the local community. The research question that arises is how the economic behavior of the consumer society network in the context of Tupperware direct selling business. The foundation of the theory which is used as a tool of analysis for this social phenomenon is Baudrillard idea about the consumer society. The research method in this study is descriptive qualitative analysis. Tupperware’s direct selling business model creates a unique networking society. The persistence of the network model of consumption, grow and develop to answer community needs that move from use value to sign value. The sign perpetuates the consumption through a variety of economic behavior. Economic behavior which appears is not only about how the network is formed in the consumer society, but also closely related to the formation stimulant consumerism to maintain the existence of this group.